Changing Trends of Major Communicable Diseases in Karnali Province of Nepal: A Descriptive Review - Paudel, Thuma Kumari; Adhikari, Govinda Prasad (Journal of Educational Research and Innovation, 2025)
Several communicable diseases have been actively impacting the health of people in Karnali province. Due to several reasons, some diseases are difficult to control and which impacts the mortality and morbidity in the Karnali province. This article aims to explore changing trends of communicable diseases in rural Nepal. This article has used a descriptive method, and data have been collected from a desk review related to communicable diseases. The information is mainly used from the national level health survey, like Nepal Living Standard Survey (2023), Nepal Demographic and Health Survey (2022), Health Service Directorates (2024), Department of Health Services (2025), National Housing and population census (2021), and other published and unpublished national and international publications. This study has used the last five years’ data, related to communicable diseases of Karnali Province only. The data was analyzed descriptively and presented in graphs and tables, providing insights into the socio-economic factors. Tuberculosis and HIV/AIDS are major issues in Karnali province. Others are Malaria, Leprosy, Dengue, and Kala-azar. The province uses several IEC and health insurance programs, but due to the changing climate, population migration, and overcrowding, disease control is not effective. Therefore, it is suggested that multi-sectoral collaboration covers the challenges.